ARRANJOS COMUNITÁRIOS ALTERNATIVOS CATÓLICOS NA REGIÃO DO GRANDE ABC: ANÁLISE SOCIOLÓGICA DE UM TIPO DE CATOLICISMO NA MODERNIDADE CONTEMPORÂNEA - RAMOS, Vlademir Lucio (2013)
This thesis examines four groups of lay catholic communities on the greater ABC region to wich we denominate Catholic Community alternative arrangements. They are extra parochial communities formed by a founder, autonomously organised with regard to a moral system, cultual, symbolical, and of a network relationship. Attuned to contemporary modernity and beneath supervision of the local clergy, these catholic arrangements are characterized by a ruled and hierarquical life, focused on serving a specific target audience, recovering, adjusting, combining religious Catholic doctrine to glossolalia practice, deliverance and soul healing. The organizational structures of the arrangements, the socio-religious antecedents of its members also their ability to adapt forward to social surroundings, were analyzed through an ethnographic research. It was found that these Catholic arrangements are places that allow their leaders to exercise at best autonomy its catholicity in a more intimate and spiratualized character. We understand t hat these Catholic arrangements composse certain type of Catholicism's consultancy that assist its clients in the "inner healing", at the same time that, devices or helpers to Catholic Apostolic Church, in order to keep it strategically in contemporary modernity. The elements that give cohesion and symbolic strength to this communities were analyzed with Bourdieu's and Durkheimian’s categories. Elements such as websites, badges and saints bastions, have become important referential that guide the daily life of the Catholics arrangements